USER ANALYSIS FOR E-INCLUSION IN A BLENDED LEARNING COURSE DELIVERY CONTEXT - Vitolina, Ieva; Kapenieks, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The authors’ purpose was to analyse users of the blended e-learning course “Improvement of ICT skills” in context of e-inclusion and determine indicators for e-inclusion facilitation. We applied a practical use probability model to perform the analysis that identified the following factors: the degree to which the instructor was willing and able to share knowledge; the degree to which the students were interested and had the capacity to learn; and the degree to which the sponsoring organization supported and promoted learning. The study was based on evaluating a group of five hundred vocational teachers who were the learners. Our results indicated that the quality of e-learning materials and environment, instructor's support, student willingness and ability to learn were attributes that could impact learning carry-over and promoted e-inclusion.